THE CONCEPTUAL FRAMEWORK OF SOCIAL INNOVATION IN SOCIAL ENTERPRISE - Nur Azura Sanusi; Suhal Kusairi; Mohd Fikri Mohamad (Faculty of Economics and Business, University of Muhammadiyah Malang, 2017)
The purpose of this paper is to study the implementation of social enterprise towards empowering the wellbeing of bottom 40 group (B40) in Malaysia. It provides an overview of the existing literature in this subject area and focuses on the ability of social innovation in empowering the B40 group. Thus, in order to elevate the B40 groups towards a middle-class society, three strategies were identified in the 11th Malaysia Plan (11th MP). One of the strategies is by developing community and social-based enterprises. As stated in 11th MP, a systematic approach shall be introduced to develop community and social enterprise based on the cooperative model to carry out activities for B40 groups in urban areas. By applying the principles of social innovation into the social enterprise framework, it can move social innovators towards sustainability and self-sufficiency. This conceptual paper contains definitions, concepts, and also the characteristics of building social enterprise in businesses with emphasis on social innovation. In addition, it also states the development of basic concepts, instruments, and dimensions in social innovation principles, and also discusses strategic and systematic plans for the B40 community. Results indicated that social innovation is important in empowering the B40 community through social enterprise and can give more impact to fulfill social needs in Malaysia.